A 'heavy hammer to crack a small nut'? The creation of the European Molecular Biology Conference (EMBC), 1963–1970. - Cassata, Francesco (Annals of Science)
This article reconstructs the complex diplomatic negotiations that led to the peculiar organization of molecular biology at the European level, by focusing in particular on the establishment of the European Molecular Biology Conference (EMBC), the intergovernmental structure founded in 1969–70 to support the scientific program of the European Molecular Biology Organization (EMBO). By combining the analysis of the informal decision-making kept in the Nobel Prize laureate John C. Kendrew's personal papers (Oxford) with the in-depth exploration of the institutional documentation available in the EMBO and CERN archives (Heidelberg and Geneva) and the Swiss Federal Archives (Bern), the article sheds light on the importance of the EMBC not only for the construction of molecular biology as a scientific, social, and political field in the European context, but also for the broader process of definition of the European research policy. Far from being just a mere replica of CERN, the EMBO/EMBC inaugurated in fact an alternative and flexible 'bottom-up' model of science policy in the European context, based on competition, networking, and scientific excellence, which paved the way to the establishment of the European Research Council (ERC) in the early 2000s.